Pengaruh Persepsi Harga Dan Lokasi Terhadap Keputusan Pembelian - Ulul Absor; Sri Rahayu; Muh. Sahidun; Mohammad Sya’bani; Apriyani .; Ilham Akbar Ashari (CV. ITTC INDONESIA, 2026)
The massive expansion of modern retail currently poses a serious threat to the existence of traditional markets, which are starting to lose their competitiveness. This study aims to analyze the influence of price perception and location on consumer purchasing decisions at Bulakamba Market to formulate strategies for sustaining the people's economy. Using a quantitative causality approach, primary data were processed using multiple linear regression analysis to accurately test the relationships between variables. Field findings prove that price perception and location have a significant positive impact with a significance level of 0.000. Individually, price perception emerged as the most dominant variable with a t-value of 6.428, while the location factor recorded a value of 4.512. This model generated a coefficient of determination of 0.657, indicating that the contribution of these two variables reaches 65.7% in triggering transactional actions. These results confirm that sensitivity to costs and ease of physical access remain the main pillars for traditional market consumers. The implications of the research demand a synergy between low-price policies and the optimization of location infrastructure to maintain customer loyalty amidst modern business competition.